WAYS TO OPTIMIZE TRAINING PLANS TO ACHIEVE A HIGH RESULT IN PARA-ATHLETICS (World Bulletin of Physical Education and Sports Science, 2026)
Para-athletics has seen rapid growth and increasing competitiveness in international competitions. Achieving high performance requires individualized training programs that consider athletes’ functional impairments, biomechanical efficiency, and physiological adaptation. Traditional training often fails to address these unique needs, limiting athletes’ performance potential.
Keywords: Para-athletics; Training optimization; Individualized load management; Sprint performance; Jump performance; Functional strength; Biomechanical feedback; Recovery strategies.